The CD28-Transmembrane Domain Mediates Chimeric Antigen Receptor Heterodimerization With CD28 - Muller, Yannick D.; Nguyen, Duy P.; Ferreira, Leonardo M. R.; Ho, Patrick; Raffin, Caroline; Valencia, Roxxana Valeria Beltran; Congrave-Wilson, Zion; Roth, Theodore L.; Eyquem, Justin; Van Gool, Frederic; Marson, Alexander; Perez, Laurent; et al. (Frontiers in Immunology, 2021)
Anti-CD19 chimeric antigen receptor (CD19-CAR)-engineered T cells are approved therapeutics for malignancies. The impact of the hinge (HD) and transmembrane (TMD) domains between the extracellular antigen-targeting and the intracellular signaling modalities of CARs have not been systemically studied. Here, a series of 19-CARs differing only by their HD (CD8, CD28, or IgG4) and TMD (CD8 or CD28) was generated. CARs containing a CD28-TMD, but not a CD8-TMD, formed heterodimers with the endogenous CD28 in human T cells, as shown by co-immunoprecipitation and CAR-dependent proliferation to anti-CD28 stimulation. This dimerization was dependent on polar amino-acids in the CD28-TMD and more efficient with CARs containing CD28 or CD8 HD than IgG4-HD. The CD28-CAR heterodimers did not respond to CD80 and CD86 stimulation but significantly reduced CD28 cell-surface expression. These data unveil a fundamental difference between CD28- and CD8-TMDs and suggest that CD28-TMD can modulate CAR T-cell activities by engaging endogenous partners.